Introduction to concurrency in programming languages - Sottile, Matthew J. (2010)
"Exploring how concurrent programming can be assisted by language-level techniques, Introduction to Concurrency in Programming Languages presents high-level language techniques for dealing with concurrency in a general context. It provides an understanding of programming languages that offer concurrency features as part of the language definition
Includes bibliographical references and index. - Print version record
Keywords: Programming languages (Electronic computers); Parallel processing (Electronic computers); Parallélisme (Informatique); COMPUTERS; Programming Languages; General; OpenMP; ERLANG; Parallelverarbeitung; Programmiersprache